Effectiveness of Self-management Interventions Based on Cognitive-behavioral Group Therapy on Life-style Among Adults With Metabolic Syndrome: A Randomized Clinical Trial - Ali Delshad Noghabi; Mohammad Hossein Bayazi; Ali Reza Rajaei (Gonabad University of Medical Sciences, 2021)
Background: Metabolic syndrome is an asymptomatic disorder and an important risk factor for cardiovascular disease and type 2 diabetes. Lifestyle modification and self-management of health-promoting behaviors are the most important actions to control metabolic syndrome. This study was done to investigate the effectiveness of self-management interventions based on group Cognitive-Behavioral Therapy (CBT) on lifestyle among adults with metabolic syndrome. Methods: This research was a randomized clinical trial study. First, 80 adults with metabolic syndrome were selected using the convenience sampling method, and then, using the randomized blockchain method, they were divided into two groups of 40 people (intervention and control groups). Data collection using the Health Promotion Lifestyle Profile II Questionnaire (HPLP II) was performed in two stages before and three months after the intervention. Teaching self-management interventions based on cognitive-behavioral therapy was done twice a week for eight 90-minute sessions. Data were analyzed using the Chi-square test, independent t-tests, and Analysis of Covariance (ANCOVA). A P-value less than 0.05 was considered significant. Results: the results of ANCOVA showed that self-management intervention based on group CBT had a significant effect on the dimensions of lifestyle, including exercise and physical activity with an effect size of 0.51, nutrition with 0.49, health responsibility with 0.39, and stress management with 0.32 (P<0.05), but it did not significantly affect the two dimensions of self-actualization and spiritual growth (effect size= 0.003, P=0.669) and interpersonal relationships (effect size= 0.029, P=0.151). Conclusion: Self-management interventions based on group CBT can improve lifestyle and some dimensions in adults with metabolic syndrome. Identifying people with metabolic syndrome and performing effective interventions with the active participation of the individual through self-management based on cognitive-behavioral therapy seem necessary.